Path analysis of the relationship between religious coping, spiritual well-being, and family resilience in dealing with the COVID-19 pandemic in Indonesia - Yoyok Bekti Prasetyo; Faridi Faridi; Nur Lailatul Masruroh; Nur Melizza; Aggraini Dwi Kurnia; Sri Sunaringsih Ika Wardojo; Titih Huriah; Rusnani AB Latif (Wolters Kluwer Medknow Publications, 2024)
Introduction: Family resilience is strongly influenced by religious coping and spiritual/religious well-being (RW). In the context of the COVID-19 pandemic in Indonesia, this study intends to investigate the relationship between religious coping, spiritual well-being, and family resilience. Methods: A cross-sectional survey (n = 242) was conducted from December 2021 to January 2022 in Indonesia. The Spiritual Coping Strategies Scale-Chinese version, Spiritual Well-Being Scale, and Family Resilience Assessment Scale were used for data collection. Smart Partial Least Square (SmartPLS) software (version 3.2.7) was used to analyze the data. Results: Most respondents aged range from 46 to 55 years-old (30.9%). Also, most of them were having senior high school educational level (47.7%), earn <3 million rupiah (90.5%), and jobless (66.7%). Family resilience to COVID-19 has been influenced by the relationship between RW and existential well-being (EW) (81.2%) (β =0.901, t = 24,836, P = 0.001). Religious Non-coping (RNC)- Religious well-being(RW) is 0.124, which indicating that RNC affecting RW by 12.4%, and it also impacting on family resilience to COVID-19 (β = −0.310, t = 3.275, P = 0.001, f2 = 0.085; minor). Conclusion: Religious coping, RW, and EW are all important factors influencing family resilience during the COVID-19 pandemic. Currently, the COVID-19 pandemic has ended. However, with the dynamic development of world health, an outbreak may occur in the future, so the findings of this research will be helpful in providing a warning about spiritual factors that significantly influence family resilience.